O Prêmio Nobel De Física De Richard Feynman: Uma Interpretação Das Matérias Jornalísticas No Brasil - (:unkn) unknown (UNIVERSIDADE FEDERAL DO OESTE DO PARÁ, 2024)
The Nobel Prize, the world's highest award in science, celebrates excellence in research and recognizes discoveries, inventions and improvements that benefit humanity. The way in which these awards reach society is usually through mass media, such as the internet, radio, television and newspapers. In view of this, this study aims to verify how the Nobel Prize in Physics, awarded to Richard Feynman, was reported in the media in our country. To carry out this study, a documentary research was conducted on the website of the Hemeroteca Digital do Brasil, in media outlets belonging to the Brazilian states, related to the Nobel Prize in Physics that Richard Feynman was awarded. Therefore, this award highlights the importance of the contributions of these scientists to the advancement of knowledge and fundamental theories of physics. Feynman's work was highlighted by newspapers for its impact on modern physics and his contributions to the development of quantum electrodynamics, revolutionizing the understanding of the interaction between light and matter
Keywords: Richard Feynman; Prêmio Nobel de Física.; Jornais; CIÊNCIAS EXATAS E DA TERRA